Pemberdayaan Warga Sekolah dan Orangtua Murid Dalam Manajemen Pengembangan Kurikulum Di Sekolah Dasar - Siti Nurrohmah (Media Manajemen Pendidikan, 2019)
This research aims at knowing (1) the empowerment of the school community and students' parents in planning; (2) organizing; (3) implementing; (4) monitoring; (5) recognizing the obstructing and facilitating factors. The research employs a qualitative approach. The implementation took place in SD 1 Pedes Argomulyo Sedayu Bantul. This research derives its data from informants consisting of headmaster, teachers, staff, students and students' parents. Technic used to gather data include interviews, observation, and document data. For the purpose of data legitimation, source triangulation, technic triangulation and triangulation time were used. Data analysis was conducted starting from data gathering, data reduction, data presentation, and drawing conclusions. Results from the resersch, in general, conclude that the empowerment of school community and students' parents in (1) curriculum-developing planning has been running very well which is displayed in establishing goals and objectives, analysis of requirements, training strategies, resources, achievement indicators, and evaluation, (2) in curriculum-developing organization in SD 1 Pedes has been running very well which is displayed in divisions of tasks, responsibilities, and authorities, the establishment of organizational structure and task division, (3) in realizing curriculum development has been running very well which is displayed in the arrangement of learning plan, the elaboration of study material, strategy, and method, provision of resource, equipment, means, scoring, environment setting, and resource utilization, (4) in evaluating curriculum development in SD 1 Pedes has been running very well which is objective, comprehensive, cooperative, efficient, relevant, sustainable, responsible, feasibility-complying, and moving toward goals, (5) the obstructing factors found during the research in the empowerment of school community and students' parents in curriculum-developing management in SD 1 Pedes include fewer awareness among certain part of teachers in developing curriculum, most students' parents are manual workers thus reluctant to contribute to brainstorming in curriculum development. The facilitating factors, on the other hand, are facilities and infrastructures belonging to SD 1 Pedes are in full and complete manner and students' parents are really supportive of curriculum development.